2020
DOI: 10.1002/cam4.2880
|View full text |Cite
|
Sign up to set email alerts
|

Study on the targeted therapy of oral squamous cell carcinoma with a plasmid expressing PE38KDEL toxin under control of the SERPINB3 promoter

Abstract: Oral squamous cell carcinoma (OSCC) has a poor prognosis and a high risk of recurrence. To improve the efficacy of OSCC therapy, it is of great significance to explore gene therapy for OSCC. The use of specific genes to regulate the targeted expression of suicide genes is a hot topic in gene therapy for cancer. The SERPINB3 gene is highly active in squamous cell carcinoma, but nearly undetectable or present at a low level in normal tissues. This specificity suggests that the SERPINB3 promoter can be used for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Such chimeric molecules are called immunotoxins (ITs) ( 11 ). In the latter strategy, the coding sequence of a toxic protein is cloned under the control of a tumor-specific promoter and delivered to cancer cells ( 12 ). Tumor-specific promoters are derived from genes that are specifically and ectopically overexpressed in cancer cells ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such chimeric molecules are called immunotoxins (ITs) ( 11 ). In the latter strategy, the coding sequence of a toxic protein is cloned under the control of a tumor-specific promoter and delivered to cancer cells ( 12 ). Tumor-specific promoters are derived from genes that are specifically and ectopically overexpressed in cancer cells ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…SERPINB3 promoter activity was detected by luciferase assay and the suicide vector pSERPINB3-PE38KDEL was tested in the SERPINB3-positive TCA8113 cell line, and in the controls. Transfection of the pSERPINB3-PE38KDEL plasmid effectively inhibited cell proliferation and induced cell apoptosis, with no signifi-cant damage to MG63 and L02; however, a transwell invasion assay showed that significantly fewer TCA8113 cells than MG63 cells passed through the gel matrix following pSERPINB3-PE38KDEL transfection [37].…”
Section: Pseudomonas Exotoxin A/pe38-based Suicide Gene Therapy Appro...mentioning
confidence: 95%